Design and Prototype of a Solar Array Malfunction Identification System. - Wabuyi, Richard (Kabale University, 2024)
The growing adoption of solar energy as a sustainable power source highlights the importance of effective maintenance strategies to maximize the performance of photovoltaic systems. This report introduces the design and prototype of a Solar Array Malfunction Identification System (SAMIS), developed to enhance the reliability and efficiency of solar installations. SAMIS integrates cutting-edge monitoring technologies and data analysis algorithms to detect, diagnose, and report issues within solar arrays. The system identifies problems such as diminished power output, module shading, and electrical faults using real-time performance monitoring and anomaly detection. By harnessing sensor data, SAMIS delivers early warning signals and actionable insights, facilitating prompt interventions and minimizing system downtime. The report details the design process, including hardware selection, software development, and system integration, alongside testing results that validate the system's effectiveness across various operational conditions. SAMIS represents a significant innovation in solar array maintenance, offering a scalable solution to enhance the longevity and efficiency of solar energy systems.